2014
DOI: 10.1111/cbdd.12267
|View full text |Cite
|
Sign up to set email alerts
|

Benzocaine Complexation with p‐Sulfonic Acid Calix[n]arene: Experimental (1H‐NMR) and Theoretical Approaches

Abstract: The aim of this work was to study the interaction between the local anesthetic benzocaine and p-sulfonic acid calix[n]arenes using NMR and theoretical calculations and to assess the effects of complexation on cytotoxicity of benzocaine. The architectures of the complexes were proposed according to (1) H NMR data (Job plot, binding constants, and ROESY) indicating details on the insertion of benzocaine in the cavity of the calix[n]arenes. The proposed inclusion compounds were optimized using the PM3 semiempiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 49 publications
3
5
0
1
Order By: Relevance
“…The stability constants of the complexes were detected using methods detailed previously [31,70,71] to be 5.07 × 10 4 M −1 and 6.3 × 10 4 M −1 which correspond to complexation free energy of −6.39 and −6.52 kcal/mol, for oxaliplatin/p-SC4, and oxaliplatin/p-SC6, respectively. These values are within the range of the stability constants (0.01 × 10 3 -1.7 × 10 5 ) M −1 previously reported for host-guest complexes, many of which are proposed for drug delivery, and many of them showed improved bioavailability, stability, and enhanced therapeutic effects [31,[72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Uv-vis Spectroscopysupporting
confidence: 84%
“…The stability constants of the complexes were detected using methods detailed previously [31,70,71] to be 5.07 × 10 4 M −1 and 6.3 × 10 4 M −1 which correspond to complexation free energy of −6.39 and −6.52 kcal/mol, for oxaliplatin/p-SC4, and oxaliplatin/p-SC6, respectively. These values are within the range of the stability constants (0.01 × 10 3 -1.7 × 10 5 ) M −1 previously reported for host-guest complexes, many of which are proposed for drug delivery, and many of them showed improved bioavailability, stability, and enhanced therapeutic effects [31,[72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Uv-vis Spectroscopysupporting
confidence: 84%
“…This might be due to the fact that in the larger SC[n]A (i.e.,S C[8]A), the cone is more flexible, which made it easier for the hydrogen bonding and electrostatic interactions to occur. [29] Because all of the binding sites on Ab 42 are limited, the number of bindings ites decreased as the calixarene size increased ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Noncovalent encapsulation of drugs into CA cavities has been widely used to improve drug properties (e.g.s olubility and stability) and/or realize drug delivery. [102] Menon et al reported the complexation of 1 and 2 with carvedilol (CDL), apoorly water-soluble drug, revealing that this complexation greatly increased CDL solubility and demonstrating al inear relationship between CDL solubility in water and CA concentration. [103] Amphiphilic CAsc an self-assemble as nanoparticles and act as drug nanocarriers.R aston et al reported that vesicles formed by amphiphilic phosphonomethyl C4A (47 in Scheme 6) effectively bind carboplatin and increase its anticancer efficacy.…”
Section: Drug Loading Within the Cavitymentioning
confidence: 99%